إدماج تكنولوجيا المعلومات والاتصال في التعليم : توصيات ومقترحات - Fatimah Ahmad Thahir (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2014)
Abstract: This research aims to uncover the benefits of the introduction of information and communication technology in education. The researcher analyzes documents from formal and non-formal institutions in facilitating the use of information and communication technology to meet the needs of today's students. In order to maximize the benefits of having ICT in education, universities have to have more interactions with the world community through communication with pople in the community and their leaders. The universities should also take advantages of available possibilities to ensure the comprehensive and sustainable development, which we desperately need them at this critical juncture for our just cause. DOI: 10.15408/tjems.v1i1.1122